2018
DOI: 10.1007/s00384-018-3069-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interleukin-6 and its soluble receptor components sIL-6R and sgp130 as markers of inflammation in inflammatory bowel diseases

Abstract: PurposeInterleukin-6 (IL-6) production and signalling are increased in the inflamed mucosa in inflammatory bowel diseases (IBD). As published serum levels of IL-6 and its soluble receptors sIL-6R and sgp130 in IBD are from small cohorts and partly contradictory, we systematically evaluated IL-6, sIL-6R and sgp130 levels as markers of disease activity in Crohn’s disease (CD) and ulcerative colitis (UC).MethodsConsecutive adult outpatients with confirmed CD or UC were included, and their disease activity and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
(70 reference statements)
3
34
0
Order By: Relevance
“…We found serum IL-6 significantly higher in CD patients with active than inactive disease ( Table I ). The ratio of median serum IL-6 in active and inactive CD of 2.12 was similar to that reported by Mavropoulou et al [ 25 ], but lower than in a study by Nikolaus et al [ 24 ]. Diagnostic performance of IL-6 in differentiating active and inactive disease was in our study worse than that of CRP ( Table II ).…”
Section: Discussionsupporting
confidence: 88%
“…We found serum IL-6 significantly higher in CD patients with active than inactive disease ( Table I ). The ratio of median serum IL-6 in active and inactive CD of 2.12 was similar to that reported by Mavropoulou et al [ 25 ], but lower than in a study by Nikolaus et al [ 24 ]. Diagnostic performance of IL-6 in differentiating active and inactive disease was in our study worse than that of CRP ( Table II ).…”
Section: Discussionsupporting
confidence: 88%
“…There have been many experimental evidence suggesting that various inflammatory mediators or markers, such as tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), and interleukin-6 (IL-6), are substantially elevated in LPS-stimulated macrophagocytes [ 13 15 ]. IL-6, a central proinflammatory cytokine that is considered a key hallmark of inflammation in the body, is known to be promptly produced in response to infectious factors and tissue injuries and can regulate intracellular signal transduction and affect other cytokines [ 16 – 19 ]. Most importantly, the acute expression of IL-6 has been reported to be a critical driving factor for many diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that brosis depends on IL-6 (13) , which increases rapidly under stress, and IL-6 is almost always increased in chronic in ammation (14) . In this study, IL-6 in BO group was signi cantly higher than that in non BO group.…”
Section: Discussionmentioning
confidence: 99%